Tindak Pidana Penyalahgunaan Senjata Api dan Senjata Tajam Dalam Undang-Undang Darurat No. 12 tahun 1951 dikaitkan dengan Faktor Korelatif Kriminalisasi - Leonardus Agung Putra Utama; Febby Mutiara Nelson (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
The main difference between the Emergency Law 12/1951 and the law that came before it is how punishments work. A sentence of 4 (four) years will be given if someone transfers guns without permission from the Chief of Police in Article 4c and Article 3 of Law 8 of 1948. When it comes to the Emergency Law 12/1951, it is punishable by death, life imprisonment, or a temporary prison sentence of up to twenty years. The difference in punishments is big because of the state's security situation at the time the emergency law was passed. However, do these sanctions still make sense in light of the current situation? People who do this kind of research call it "normative" or "library law research." When reviewing and analyzing library materials or secondary data that are related to research materials, the normative approach is used. This approach is used to look at primary legal materials, secondary legal materials, and third-party legal materials. Other laws and regulations that deal with guns and sharp weapons, like Regulation of the Head of the Indonesian National Police Number 18, 2015, which deals with licensing, supervision, and control of non-organic firearms of the Indonesian National Police/Indonesian National Armed Forces for Self-Defense and Regulations of the Head of the Indonesian National Police.Keywords: Firearms; Sharp Weapons; Criminalization AbstrakPerbedaan antara Undang-Undang Darurat 12/1951 dengan Undang- Undang sebelumnya yang paling terlihat adalah tentang sanksi. Sebagai contoh, dalam Pasal 4c jo Pasal 3 UU No. 8 Tahun 1948 bila terjadi pemindahtangan senjata api tanpa tanpa ijin dari Kepala Kepolisian maka akan dikenakan pidana selama 4 (empat) tahun. Sementara dalam Pasal 1 ayat (1) UU Drt 12/1951, dihukum dengan hukuman mati atau hukuman penjara seumur hidup atau hukuman penjara sementara setinggi-tingginya dua puluh tahun. Perbedaan sanksi yang signifikan mengingat situasi keamanan negara pada saat dibuatnya UU darurat. Namun apakah sanksi tersebut masih relevan bila dibandingkan dengan kondisi saat ini. Metode yang digunakan dalam penelitian ini adalah penelitian hukum normatif atau penelitian hukum kepustakaan. Peraturan mengenai sejata api dan senjata tajam selain Undang- Undang Darurat 12/1951 seperti contohnya Peraturan Kepala Kepolisian Negara Republik Indonesia Nomor 18 Tahun 2015 Tentang Perizinan, Pengawasan dan Pengendalian Senjata Api Non organik Kepolisian Negara Republik Indonesia/ Tentara Nasional Indonesia untuk Kepentingan Bela Diri dan Peraturan Kepala Kepolisian Negara Republik Indonesia.enjaKata Kunci: Senjata Api; Senjata Tajam; Kriminalisasi